Presentasi Diri Remaja Akhir dalam Membangun Identitas Diri di Media Sosial Tiktok di Kecamatan Soreang Kabupaten Bandung - Nizad Naufal Fachrezi; Rodhiyat Fajar Salim; Imam Jahrudin Priyanto (GLOBAL SCIENTS PUBLISHER, 2026)
TikTok has developed into a digital communication space as well as a stage where late adolescents display, construct, and maintain their self-identity in front of an audience. This study aims to understand how late adolescents in Soreang District, Bandung Regency, use TikTok as a medium for self-presentation through the concepts of front stage, backstage, and impression management in constructing self-identity. Erving Goffman's (1956) Self-Presentation Theory through a dramaturgical approach is used as the analytical framework. This study employs a qualitative method with a phenomenological approach and a constructivist paradigm. Data collection techniques included observation of informants' TikTok accounts, in-depth interviews, documentation studies, and triangulation of sources, techniques, and time involving five late adolescents aged 17-24 residing in Soreang District who actively produce content on TikTok. The results show that in the front stage dimension, informants consciously manage setting, appearance, and manner to display an identity aligned with their respective interests and personalities. In the backstage dimension, informants keep most of their personal lives beyond the audience's reach, creating a clear separation between digital identity and daily life. Meanwhile, in the impression management dimension, informants consistently manage messages, appearance, and responses to audience feedback without altering their basic character. This study concludes that TikTok functions as a digital stage that enables late adolescents to actively construct and negotiate their self-identity through the process of self-presentation.